Intégrer l’éducation à l’environnement dans les pratiques d’alphabétisation populaire au Québec - Carine Villemagne; Justine Daniel; Lucie Sauvé; Kaven Joyal (VertigO)
Environmental education (EE) is an essential dimension of education. Well developed for young people, EE for adults is underdeveloped especially in non-formal educational contexts. As we started to work with adult literacy community groups in Quebec, we investigated possibilities to integrate EE in adult literacy practices. First, we highlighted environmental conceptions and concerns of adult learners engaged in adult literacy practices, as well as we explored their own environmental acts. Second environmental and EE needs and expectations of these adults were discussed. The outcomes of our investigation supply interesting information for integrating EE in adult literacy practices that will be adapted and relevant for adult literacy community groups in Quebec. As examples, it seems essential to take into account environmental adult knowledges and their way of learning that are adapted of their low levels of reading and writing.